Wielojęzyczność w reklamie - nadawca i narracja - Wyrwas, Katarzyna (Stylistyka, 2021)
The author treats multilingualism as the way of constructing oftext structure. Multilingualism in television commercial spot can be describing on severa! areas: spots use many codes ( verba!, visual and sound code ), have many speakers, can have many ways of speaking and use many genres of speech. This article has two main aims. First aim is to describe multilingualism in quasi-dialog of speakers as a harmony of voices which is presenting product. Second aim is to show multilingualism considered as genres of speech combination. Author presents how conversional, everyday narrative exists in commercial text. Everyday narrative is spoken by the speaker which is similar to receiver. Narrative helps to built commercial’s credibility. It causes increase of consumer’s confidence to the otfered product.